The Polak’s monetary model and its application on Macedonian case - Gockov, GJorgji (Institute of Knowledge Management Skopje, 2019)
Macroeconomic stability is very important for each economy because it constitutes the basis of sustainable economic growth and development. It means stable prices with a low level of inflation (internal stability), a stable foreign exchange rate, a relatively low and sustainable current account deficit in the balance of payments and a solvent position in the external indebtedness of the economy (external stability). International Monetary Fund (IMF) provides financial support to countries that have problems with internal and external stability. The IMF approach to macroeconomic stabilization is based on a so-called “monetary approach” to the balance of payments. The first IMF model designed for dealing with balance of payments disequilibrium was the Polak’s model on monetary programming. Its purpose is to integrate monetary, income and balance of payments analysis, and it represents the basis of the conditionality applied to IMF’s credit arrangements. This model investigates and determines the effect on income and balance of payments arising from the two important variables in the economy: (1) changes in domestic bank credits, and (2) changes in exports of goods and services. In other words, the model indicates what macroeconomics policies are required to achieve a given set of outcomes i.e. it determines policy targets consistent with explicit macroeconomic objectives. It consists of a set of four equations and contains two behavioral relationships: the demand for money function and the function of the demand for imports, and two identities: for the money supply and for the balance of payments. As such, Polak's monetary model extends classical quantitative money theory to the example of an open economy. Republic of North Macedonia, as a developing country that is remarkably open to the world (large share of export and import of goods and services in GDP) and with close cooperation with the IMF, the application of so-called financial programming based on Polak’s monetary model is of special importance. Based on the theoretical elaboration of the equations contained in the Polak’s monetary model, the paper attempts for its application to the case of Republic of North Macedonia and tries to determine and quantify the dependence of the changes in net foreign assets (foreign reserves) and gross domestic product (GDP) from the changes in domestic credits of the Macedonian banking sector. For that purpose, the data on gross domestic product (GDP), money supply (M4) and exports of goods and services for the period 2003-2018 were used from the State statistical office and National bank of the Republic of North Macedonia. By calculating the values of income velocity of money and propensity to import, the interdependence of domestic credits with gross domestic product and net foreign assets of the banking sector is calculated and analyzed.
Keywords: domestic credits, balance of payments, velocity, propensity to import, net foreign assets